Implementasi Nilai Sakai Sambayan Dalam Kehidupan Sosial Masyarakat Lampung Modern - Ariyanti, Rina; Desiana Putri, Dilla (JURNAL MANAJEMEN PENDIDIKAN, 2025)
IMPLEMENTATION OF SAKAI SAMBAYAN VALUES IN THE SOCIAL LIFE OF MODERN LAMPUNG SOCIETYSakai Sambayan is a noble cultural value of the people of Lampung that describes the spirit of mutual cooperation, togetherness, and social solidarity among others. This value is the moral and social foundation in various aspects of the life of the people of Lampung, both in customary, social, and religious activities. This study aims to describe how the values of Sakai Sambayan are applied in the life of the modern Lampung people, as well as identify the factors that support and hinder its implementation in the midst of rapid social change. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study show that the value of Sakai Sambayan is still maintained and applied in various community activities, such as mutual cooperation in improving public facilities, the implementation of traditional ceremonies, religious activities, and social collaboration in the digital space through online fundraising and community-based social actions. Factors that support the preservation of these values include the strong internalization of local culture in daily life, the active role of traditional and religious leaders, and the support of families and educational institutions in instilling the value of togetherness. However, the application of Sakai Sambayan values faces a number of challenges, such as the increase in individualism due to modern lifestyles, the influence of urbanization that weakens social ties, and the declining participation of the younger generation in traditional social activities. Therefore, the preservation of Sakai Sambayan values needs to be done in an adaptive and innovative manner to remain relevant in the modern era through education, digital media, and community-based social activities.